Le paysage agricole comme médiation dans la communication du parc naturel régional du Pilat - Émilie Kohlmann (Projets de Paysage)
This article is a part of an information and communication science research study and is based on the analysis of communication documents produced by the Pilat Regional Nature Park from 2010 to 2015. The study focuses on how landscapes are used to illustrate certain principles and actions on the part of the park authorities. Their representation in institutional communication documents highlights the mediating role played by these authorities. The representations of farming landscapes used serve in mediating between positions which are frequently and historically in conflict, such as the defense of the environment, heritage conservation, economic development, and professional farming practices. The communication strategy of the park authorities makes it possible, by employing representations of the farming landscape and of ordinary nature, to reconcile the positions of the park’s different stakeholders such as local inhabitants, tourists, nature lovers and farmers.